Refining constitutive relation by integration of finite element simulations and Gleeble experiments. Issue 6 (June 2019) - Yu, D.J.; Xu, D.S.; Wang, H.; Zhao, Z.B.; Wei, G.Z.; Yang, R.
Abstract: Thermo-mechanical coupled finite element calculations were carried out to simulate the Gleeble compression of the samples of a titanium alloy (Ti60), and the results are analyzed and compared with the actual compression tests conducted on a Gleeble 3800 thermo-mechanical simulator. The changes in temperature, stress and strain distribution in the samples and the source of error on the constitutive relations from Gleeble hot compression test were analyzed in detail. Both simulations and experiments showed that the temperature distribution in the specimen is not uniform during hot compression, resulting in significant deformation inhomogeneity and non-ignorable error in the flow stress strain relation, invalidating the uniform strain assumption commonly assumed when extracting the constitutive relation from Gleeble tests. Based on the finite element simulations with iterative corrections, we propose a scheme to refine the constitutive relations from Gleeble tests.